PENGARUH MEDIA FLASH CARD TERHADAP KETERAMPILAN MEMBACA PERMULAAN PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS II MI Al-FATAH SINGKAWANG - Nurnabila; Wahyuni Oktavia; Lili Yanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to (1) determine the differences in initial reading skills betweenclasses that use flash card media and classes that do not use flash card media inthe Indonesian language subject of class II students at MI Al-Fatah Singkawang,(2) determine how much influence flash card media has on initial reading skills inthe Indonesian language subject of class II students at MI Al-Fatah Singkawang,(3) determine students' responses to the use of flash card media in learningIndonesian language of class II students at MI Al-Fatah Singkawang. This type ofresearch is quantitative with a quasi-experimental method with a non-equivalentpre-test and post-test control group design. The population in this study were all 45second-grade students of MI Al-Fatah Singkawang. Sampling in this study usedsaturated samples (total sampling). Data collection techniques in this study weretest and non-test techniques. The data analysis technique used was statisticalanalysis. The results of the study showed that: (1) There were differences in initialreading skills between classes that used flash card media and classes that did notuse flash card media in the Indonesian Language subject for second-gradestudents of MI Al-Fatah Singkawang, (2) The magnitude of the influence of flashcard media on initial reading skills in the Indonesian language subject of class IIstudents of MI Al-Fatah Singkawang. This is proven that the Effect Size is 1.370then ES > 0.8 which means it is included in the High criteria. (3) the studentresponse questionnaire showed a very good response, proven by the results of thepercentage calculation getting 86%.